Pengaruh Motivasi Terhadap Prestasi Belajar Mata Pelajaran Fiqih Siswa Kelas XI MA Roudlotul Muta’allimin Simbar Tampo Cluring Banyuwangi Tahun Pelajaran 2015/2016 - Al Rosid, Moh. Harun (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
The purpose of this study to determine the motivation of learning subjects fiqih class XI students in MA Roudlotul Muta'allimin Simbar Tampo Cluring Banyuwangi 2015/2016 year. To know the learning achievement of fiqih subjects of class XI students in MA Roudlotul Muta'allimin Simbar Tampo Cluring Banyuwangi 2015/2016. To know the effect of motivation on the achievement of learning subjects fiqih class XI students in MA Roudlotul Muta'allimin Simbar Tampo Cluring Banyuwangi academic year 2015/2016. This research uses quantitative method with product moment technique. Conclusion 1) Based on the t test obtained the results of student learning motivation (X) variable is fairly good; 2) Based on the t test obtained the results of student learning achievement (Y) variable is fairly good; 3) Based on the calculations performed by using a simple regression formula t arithmetic significant influence with regression coefficient of 0.140 which is pentropped to 14%. Thus there is influence of learning motivation to learning achievement equal to 14%.